SUPERVISORY CAPACITY OF FINANCIAL INSTITUTIONS IN COUNTERING CYBERCRIME AND INFORMATION ASYMMETRIES IN THE CONDITIONS OF THE GROWTH OF THE ROLE OF FINTECH AND BIG TECHS IN THE DIGITALIZED INTERNATIONAL CAPITAL MARKETS - SHLAPAK, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The request for digital sovereignty within national jurisdictions or at the level of integration associations in the context of the expansion of cyberspace and the opportunities and threats it produces should correspond with the potential of the existing digital financial infrastructure, which is global in nature, which gives FINTECH and BIG TECH tools for transformative construction of the financial market. services. The purpose of the article is to reveal the supervisory potential of financial institutions in countering digital crime and information asymmetries in the context of the growing role of FINTECH and BIG TECHS in international capital markets. The article explores the role of FINTECH and BIGTECH as a dynamically developing segment at the intersection of the financial services and technology sectors. In it, technology startups and new market entrants are taking innovative approaches to products and services currently provided by the traditional financial services sector.Today, new technologies (digital, telecommunications, biometrics, etc.) are reshaping the financial services industry, actively replacing traditional players and traditional business models. The integration of new financial solutions allows you to change the structure of consumption, reduce the cost of certain functionality (processing customer bases, loyalty programs, etc.), increase the efficiency and quality of business processes (targeting the target audience, scoring, etc.), and also significantly affect sustainability development of core business, etc. As a result, the financial technology industry is gradually turning into an independent, intensively developing sector of the modern economy. The FINTECH segment is rapidly developing, disrupting the usual order of things in the traditional value chain. Companies in the segment, using the latest technologies and new directions of activity, are reshaping the competitive landscape, blurring the boundaries that have been established among players in the financial services sector. The FINTECH ecosystem includes such elements as startups, technology companies, financial institutions and infrastructure players. FINTECH platforms operate in the most profitable part of the banking chain. Most companies in the financial technology sector operate at the so-called last mile stage, that is, at the stage of interaction with the end consumer. These services include: P2P lending platforms, money transfer and payment acceptance services for small and medium enterprises. It is these areas that are the main sources of income for traditional banks. The very financing of the FINTECH industry is often of a credit nature, and cheap borrowed resources only increased interest in such innovations. of great importance for the fintech industry is the dynamically developing e-commerce market. In particular, this factor will stimulate the growth of the volume of services in the segment of payments and transfers, as well as in the segment of financing.The article considers the phenomenon of gamification (the use of game elements), which is essentially a system of motivation and incentives, which leads to the fact that the client interacts with the financial institution more often, which makes it possible to achieve increased loyalty to the company. In the era of total digitalization, the problem of cybersecurity, protection of personal data, identification and authentication of a person in the information space when making financial transactions becomes relevant. The attention is focused on the risks of cyberattacks and theft of funds due to the disclosure of access to information systems.
Keywords: cybersecurity market; BIG TECHS; FINTECHS; financial services market; financial supervision; information asymmetries; gamification; digital capital markets; EU digital sovereignty; lending and loans